Microrespirometer chamber for determinations of viability in cell and organ cultures. - Gabridge, M G (1976)
The effects of chemical, physical, and infectious cytotoxic agents on primary and cultured cells were evaluated by measurements of oxygen uptake for various time periods. A newly developed respirometer used a Clark oxygen electrode in a 1.0-ml chamber, with provisions for constant mixing and for temperature control of both the sample and electrode chambers. The device was unique because the electrode and instrumentation were provided by a clinical blood-gas analyzer. Oxygen uptake by blank controls was negligible, whereas cells and tissue consumed oxygen at rates of approximately 1 to 5 mul/h in a dose- and temperature-dependent fashion. Cyanide, heat, and freeze-thaw lysis reduced the oxygen uptake to less than 0.6 mul/mg per h. Infection of trachea organ cultures with Mycoplasma pneumoniae significantly reduced relative ciliary activity, tetrazolium reduction capacity, and oxygen consumption in a coordinated fashion.